Analysis of"4.28"sever local storm caused stationary front of Wenshan in Yunnan Province - Ying MIN; Jihua SUN; Man WANG; Li ZHU; Zhiguo WANG; Qianyuan YANG (暴雨灾害, 2022)
Based on data from conventional observations, ERA5, intensive automatic weather stations, satellite cloud images and weather radar, a sever local storm in Wenshan on 28 April 2021 was analyzed. The results are as follows. (1) This event took place under the synoptic condition of the weaken stationary front and the strong subtropical high. Several factors, such as moderate vertical wind shear, unstable stratification and large convective available potential energy, provided favorable environmental conditions for the occurrence of storm. (2) The combined action of the surface convergence line formed by the stationary front and terrain triggered the generation of convection. The ground convergence line formed by outflow boundary of thunderstorm high and ambient wind played an important role in strengthening the storm. (3) The severe local storm was caused by single-cell storm. Radar echoes had characteristics of inclined structure, hook echo, sidelobe echo, rapid declines of the core of reflectivity factor and jumped VIL. The characteristics had a certain indication in monitoring and warning of hail.